Defect Analysis of Pepari Leather Bags Using Fault Tree Analysis and 5W+1H: Analisis Kecacatan Tas Kulit Pepari Leather dengan Fault Tree Analysis dan 5W+1H - Pradana, Billy Gandis; Rochmoeljati, Rr. (Indonesian Journal of Innovation Studies, 2025)
General Background: Leather-based products such as bags are highly valued for their aesthetic and durability, yet their production is prone to quality issues. Specific Background: A manufacturing company specializing in leather accessories has consistently encountered product defects, especially in its leather bag line. Knowledge Gap: Despite the importance of maintaining quality in leather goods, there is limited systematic analysis on the root causes of defects using structured diagnostic methods in such contexts.Aims: This study aims to identify and analyze the root causes of leather bag defects using the Fault Tree Analysis (FTA) and 5W+1H methods to propose effective corrective measures. Results: The findings reveal three major defect types: uneven leather texture (0.1018%), scratch marks (0.1577%), and stitching holes (0.1034%). Novelty: The integration of FTA with the 5W+1H framework offers a structured, diagnostic approach rarely applied in small to medium-scale leather production settings. Implications: Recommended improvements include strengthening quality control protocols, enhancing raw material inspection, maintaining equipment reliability, and implementing targeted worker training—providing a comprehensive basis for quality enhancement in leather goods manufacturing. Highlights: Identifies key leather bag defects with precise probability data. Combines FTA and 5W+1H for structured root cause analysis. Proposes actionable improvements to optimize production quality. Keywords: Fault Tree Analysis, Quality Control, Leather Bag, Defect Analysis, Root Cause